Case Study Of The Application Of Oral Motor Exercise Therapy On The Sucking Reflex In Lbw Infants In The Perinatology Room Of Dr. Soekardjo Hospital, Tasikmalaya City - Kusmana, Tatang; Hani Handayani; Sri Mulyanti; Nurwijayani, Nita (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2025)
Low Birth Weight (LBW) babies are babies born weighing between 1500 and 2500 grams, and lack of sucking reflex is one of the health problems they may experience. Early oral stimulation, such as massaging the muscle tissue around the mouth, can help overcome weak sucking reflexes. To improve the sucking reflex of patients with LBW, this study aims to apply evidence-based oral motor exercises. This study uses a case study type and is descriptive. In three days, oral motor exercises were carried out every day for fifteen minutes. The results of the study on patient after being given oral motor exercises on the first and second days the patient was still given nutrition through OGT and on the day when client had been given milk through a bottle as much as 10 cc / 3 hours, but client finished the milk as much as 5-7 cc / 3 hours. It can be concluded that the focus data of the assessment results obtained that client was medically diagnosed with LBW, OGT was installed due to weak sucking and swallowing reflexes, Patient weight was 2200 g, then the author raised the main diagnosis of nutritional deficit and disorganized infant behavior which was given oral motoric exercise, and the results obtained that oral motor exercise can increase sucking reflexes in LBW infants. With this study, the suggestion for hospital service institutions is that oral motor exercises like this can be used as an alternative to increase sucking reflexes in LBW.